Determination of Optimum Sowing Rate for Narbon Vetch (Vicia narbonensis L.) Cultivation in Antalya Coastal Conditions - Yaşar ÖZYİĞİT (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
This research was conducted to determine optimum sowing rate for narbon vetch (Vicia narbonensis L.) in Antalya coastal conditions in 2014-2015 and 2015-2016 years. The research was designed according to randomized complete block design with three replicates, and five different sowing rates (5, 10, 15, 20 and 25 kg da-1) were performed to parcels. Some agronomic data such as plant height, number of pods, number of seeds per pod, number of branches, pod length, 1000 grain weight, grain yield, biological yield, straw yield, and harvest index were investigated. Study results showed that sowing rates had statistically significant effects on all studied traits. Plant height, seed yield, biological yield and straw yield increased with increasing sowing rate, while pod number, the number of seeds per pod, number of branches, pod length, 1000 seed weight and harvest index decreased. Grain yield reached its highest value at 15 kg da-1 application and a decrease in higher seed applications were observed. When the results obtained were evaluated, it was concluded that the most appropriate sowing rate for narbon vetch cultivation in Antalya coastal conditions was 15 kg da-1 where the highest grain yield was achieved and the sowing rates above or below this value resulted in decreased yield.